(3cJGH ajg fHPI ef GdJGQjN hfHPI ef CNHGQ eUQ hYLGFHgG hZjQ Pdc eeG jSQ GdfGXQjfs
(3ChdgG (B:s
(3GdMeO ddg GdPi NU cdGe GdYQH HHOjY GdMce , bGd Efi PGcQ ai gPG GdeLehY fhGOQ ef cdGe GdaUMGA hMcGjGJ GdHdZGA s
(3Vef eLehY , JQJjHgG (B: (3ef U (B91 (3C (B- (3U(B101 (3Hs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B212 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs